An improved stator flux estimation in steady-state operation for direct torque control of induction machines - Idris, N. R. N.; Yatim, A. H. M. (IEEE, 2002)

(untitled)
This paper presents an improved stator flux estimation technique based on a voltage model with some form of low-pass (LP) filtering. In voltage-model-based stator flux estimation, an LP filter is normally used instead of a pure integrator to avoid integration drift problem due to DC offset, noise, or measurement error present in the back electromotive force. In steady-state condition, the LP filter estimator will degrade the performance and efficiency of the direct torque control (DTC) drive system since it introduced magnitude and phase errors, thus resulting in an incorrect voltage vector selection. The stator flux steady-state error between the LP filter and a pure integrator estimator technique is derived and its effect on the steady-state DTC drive performance is analyzed. A simple method is proposed to compensate for this error which results in a significant improvement in the steady-state drive performance. Simulation based on this technique is given and it is verified by experimental results